Insecticide Formulations - Bindu, S.P.; Akoijam, Romila (Indian Journal of Hill Farming, 2019)
The properties of insecticides formulations should be understood before choosing a right insecticide which was help to avoid problems and it can be applied in an effective way. The insecticides application equipment must be able to deliver the right amount of pesticide to the targeted pests. Several types of insecticide application equipments like sprayer, duster and granular applicator have different function but each equipment types have their own ways to control a particular pest. The right amount of insecticide should be properly calculated and applied on target pests in effective manner.